Peranan pertumbuhan ekonomi dalam memediasi faktor-faktor yang mempengaruhi indeks pembangunan manusia - Susila, Muktar Redy (Journal of Business & Banking, 2023)
Provincial HDI data in 2022 shows striking disparities between regions. This figure shows the uneven economic development in Indonesia. An analysis of factors that can influence HDI is needed. This research aims to analyze the influence of regional finan-cial performance and capital expenditure on HDI with economic growth as an inter-vening variable. The sample used in this research was 34 provinces that met the research criteria. The variables used in this research are regional financial performance, capital expenditure, economic growth, and HDI. Financial performance and capital expenditure are exogenous variables, economic growth is an intervening variable, and HDI is an endogenous variable. The method used to analyze the relationship between variables is SEM PLS. The test results show that financial performance, capital expenditure and economic growth directly have a positive significant effect on HDI. The results of this test have the implication that to improve the quality of life of the population, attention is needed to improve financial performance, capital expenditure and economic growth in each region. The other test results showed that economic growth was able to mediate the effect of capital expenditure on HDI but was not able to mediate the effect of financial performance on HDI.